Enhancement in microstructural and mechanical performance of AA7075 aluminum alloy via severe shot peening and ultrasonic nanocrystal surface modification - Efe, Yusuf; Karademir, İbrahim; Husem, Fazil; Maleki, Erfan; Karimbaev, Ruslan; Amanov, Auezhan; Unal, Okan; Karademir, İbrahim (Elsevier, 2020)
In this experimental study, AA7075 aluminum alloy was subjected to pure severe shot peening (SSP), pure ultrasonic nanocrystalline surface modification (UNSM) and the combination of these two treatments. The treated specimens were analyzed with detailed microstructure analysis, micro-hardness, surface roughness, XRD investigations and wear-friction tests. The results demonstrated that UNSM exhibited fine surface finish and provided minimum surface roughness with the Ra value of 0.8 limo Moreover, UNSM played an important role in the reduction of Ra as a secondary treatment. Electron back scatter diffraction (EBSD) analysis, full width at half maximum (FWHM) evaluations and compressive residual stress (CRS) measurements showed that the deformed layer structure was converted into a nanocrystallized and compressively stressed zone via SSP and UNSM. The hardness on the topmost layer was effectively enhanced by UNSM + SSP and SSP + UNSM processes. The wear and friction performance were particularly improved by two-stage operations of UNSM + SSP and SSP + UNSM. The performance was also compatible with the hardness, residual stress and nanocrystallization investigations.
Keywords: Ssp; Unsm; Wear; Grain Refinement; Nanocrystallization